REPRESENTASI NILAI FEMINISME DALAM NOVEL “AKU LUPA BAHWA AKU PEREMPUAN” KARYA IHSAN ABDUL QUDDUS - Ria Nita Anggreani; Atika Atika; Astinana Yuliarti (Bajang Institute, 2023)
This research was conducted with the aim of knowing how to represent the values ​​of feminism in the novel 'Aku Lupa Bahwa Aku Perempuan' by Ihsan Abdul Quddus. In order to examine this problem, the researcher uses a descriptive qualitative approach with a narrative analysis method using the Tzvetan Todorov model. Data collection is done by reading the entire contents of the novel and then taking several texts or narratives that contain feminism values ​​and literature studies. The results of this study indicate that feminism values ​​were represented by the author in the form of a narrative of the character's thoughts, dialogues between characters and an explanation of every event that occurs in the novel. In addition, by using a narrative analysis that divides the story into 3 (three) phases, it is known that from the initial phase (equilibrium), the chaos phase, to the final phase (equilibrium) in the novel ‘Aku Lupa Bahwa Aku Perempuan’ written by Ihsan Abdul Quddus There are several streams of feminism, including: liberal feminism, existentialist feminism, radical feminism and postmodern feminism